2021
DOI: 10.21123/bsj.2021.18.1(suppl.).0716
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Some Chemicals of Mosquitoes Culex pipiens molestus Forskal

Abstract: The chemicals materials were used to study the effect of citric acid, detergents, sodium carbonate, sodium bicarbonate on the vitality of the third stage of mosquito Culex pipiens molestus. The highest larvicidal efficacy was established from citric acid solution followed by detergents solution, sodium carbonate, sodium bicarbonate with (LC 50 ) values 2096, 2715, 13930, 13960 ppm respectively. The concentration of 1000 ppm of citric acid showed a fatal effect on the third stage larvae of mosquitoes which gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The results of this study are comparable to those of [7], who found that Larval death rates for Yil, Tar, and Ala essential oils (EOs) against Anopheles arabiensis were 81%, 80%, and 37%, respectively, at 50 μl/L concentration (The Clevenger-type device was used to extract the thyme essential oils, which were given the names Tar, Ala, and Yil). [5], reported that the citric acid solution was shown to have the highest larvicidal efficacy, followed by detergent solutions, sodium carbonate, and sodium bicarbonate, with (LC50) values of 2096, 2715, 13930, and 13960 ppm, respectively against third stage of Culex pipiens molestus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are comparable to those of [7], who found that Larval death rates for Yil, Tar, and Ala essential oils (EOs) against Anopheles arabiensis were 81%, 80%, and 37%, respectively, at 50 μl/L concentration (The Clevenger-type device was used to extract the thyme essential oils, which were given the names Tar, Ala, and Yil). [5], reported that the citric acid solution was shown to have the highest larvicidal efficacy, followed by detergent solutions, sodium carbonate, and sodium bicarbonate, with (LC50) values of 2096, 2715, 13930, and 13960 ppm, respectively against third stage of Culex pipiens molestus.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, researchers have focused on using safe, affordable alternatives to pesticides, like inorganic salts and antioxidants, which work well against insects that stay for a short time. The careful preparation of these materials results in the total elimination of insects and accomplishes the objective in small amounts and in a safe manner that doesn't risk human health [5,6]. Compounds derived from plants have a bright future as solutions to combat diseases spread by mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, these chemicals could be harmful to the environment if they end up in food waste, and they can mortality other insects that are friendly with the environment 9, 10 so, researchers recently ended up using Inorganic salts and antioxidants can be used instead of pesticides because they work just as well against insects that don't live long, are safe, and cost less. Careful preparation of this material leads to eliminate of insects and achieving the goal in small quantities and in safe substances that lead to eliminate insects in a safe way and do not harm human health 11,12 . Insect pests have been controlled in ways that are better for the environment by using traditional extracts or products made from plants instead of conventional pesticides made from chemicals.…”
Section: Introductionmentioning
confidence: 99%